Correlation study of stress biomarkers, endocrinopathies, semen quality and quantity in infertile men in Abuja, Nigeria - Peter, Abriba Simon; Humphrey B., Osadolor (International Journal of Research in Medical Sciences, 2023)
Background: The quality and quantity of sperm cells in the male determines his fertility potentials. It has been reported that 40-45% cases of infertility is attributable to men, and that stress compromises fertility indices. Therefore, the study was done to assess the correlation between some stress biomarkers, male endocrinopathies, sperm quality, and quantity in infertile men. Methods: This was a cross sectional case- control study. A total of 154 participants were recruited into the study, which consist of 100 males having the challenge of infertility as study group and 54 fertile male which serves as control group. Serum testosterone, LH, FSH, prolactin, salivary cortisol and amylase were analyzed using ELISA techniques; while the semen was examined after liquefaction according to WHO criteria. Results: In the study group, higher values of stress biomarkers correlated with significantly decreased testosterone and FSH values (p=0.001), and increased prolactin, salivary cortisol amylase (p<0,001); semen quality and quantity correlate with stress biomarkers (p<0.001). There are both positive and negative correlation between the stress biomarkers, sex hormones, sperm quality and quantity. Conclusions: Higher values of stress biomarkers in infertile male show both negative and positive correlation with abnormal sex hormones, decreased semen quality and quantity.